Design and manufacturing deployment of diesel engine common rail electronic control system - Nguyễn Kim; Lê Khánh Tân; Vũ Trọng Tài (Journal of Technical Education Science, 2018)
Currently, the field of electronic engine control technology in the world has been strongly developingand applying on vehicles and mostly in cars. In particular, the engine electronic control system is extremely important, especially for Diesel fuel systems. In technical training, learners must be familiar with structure, operation as well as inspection and collection of signals on the engine to provide diagnostic testing methods and research directions to improve the system of electronic control on Diesel engines. However, nowadays, most of departments of many universities and particularly our department of internal combustion engine are only equipped with some models of common rail Diesel engines without modules of electronic Diesel engine control systems. Thus many difficulties occur during the teaching, learning and researching of students. In order to do the project, we have studied the structure, function of the sensors, the actuators on the engine together with its basic signals, thus designing and implementing the model of Toyota Hilux electronic common rail Diesel engine. The result of the model works effectively, visually and lively for training.